Enhancing preschool children's sustainable environmental behaviors through geography-based activities - Eksi, Esra Gamze Ugur; Ozkan, Banu; Tugluk, Mehmet Nur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This study examines how geography-based activities can enhance sustainable environmental behaviors in preschool children. The research was conducted with 24 children attending a private kindergarten in Eski & scedil;ehir, Turkey. A quasi-experimental pretest-posttest control group design was employed. The experimental group participated in an eight-week geography-based environmental education program, while the control group continued with the standard curriculum. Data were collected using the Sustainable Environmental Behavior Assessment Scale for children aged 60-72 months, which consists of two subdimensions: environmental awareness and environmental consciousness. Since no significant difference was found between the groups' pretest scores, the experimental group received geography-based activities twice a week for eight weeks. At the end of the intervention, post-test results revealed statistically significant improvements in environmental awareness and environmental consciousness in the experimental group compared to the control group. However, in the control group, changes were observed only in the environmental awareness subdimension. These findings suggest that integrating geography-based activities into early childhood education enhances children's environmental responsibility and engagement in sustainability practices. Future research should investigate the long-term retention of sustainability-related behaviors and assess the effectiveness of geography-based environmental programs in diverse educational settings.
Keywords: Climate change education; environmental behavior; geography-based activities; place-based learning; preschool children; EDUCATION; Education & Educational Research